2021
DOI: 10.1186/s12889-021-10684-1
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Reduced level of physical activity during COVID-19 pandemic is associated with depression and anxiety levels: an internet-based survey

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 1 publication
5
36
1
Order By: Relevance
“…Furthermore, when compared to the world average, the prevalence of anxiety in men in the Americas region is 56% higher compared to the world average [ 1 ]. Recently, it was shown in a sample of Brazilian men that 49.1% of them have anxiety symptoms due to the COVID-19 outbreak [ 6 ]. Therefore, strategies for treating anxiety disorders in the male population are also warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when compared to the world average, the prevalence of anxiety in men in the Americas region is 56% higher compared to the world average [ 1 ]. Recently, it was shown in a sample of Brazilian men that 49.1% of them have anxiety symptoms due to the COVID-19 outbreak [ 6 ]. Therefore, strategies for treating anxiety disorders in the male population are also warranted.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent work studying youth long-distance runners found that COVID-19 social distancing restrictions impacted training habits (Bazett-Jones et al, 2020). Furthermore, recent studies have illustrated that physical activity levels during the COVID-19 global pandemic have decreased (Castañeda-Babarro et al, 2020;Gallè et al, 2020;Eek et al, 2021;Fearnbach et al, 2021;Puccinelli et al, 2021;Wilke et al, 2021). Self-reported moderate physical activity levels have been reported to decrease by 41%, while Eek and colleagues depicted that more than 65% of the participants reported changes in their physical activity (Eek et al, 2021;Wilke et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review reported significant reduction of varying degree in walking, moderate, vigorous, and total physical activity levels during the COVID-19 pandemic lockdown in college students ( 36 ). In recent years, the positive benefits of physical activity for mental health have been widely recognized ( 33 , 37 ). In response to the urgent need to improve physical activity levels, many countries including China have adopted positively physical activity strategies.…”
Section: Discussionmentioning
confidence: 99%